INNOVATIVE PEDAGOGICAL STRATEGIES FOR EFFECTIVE DIGITALIZATION OF EDUCATION IN THE UNIVERSITIES - Medeshova, Aigul; ÖZERBAŞ, Mehmet; AKIMOVA, Saule; KURMASHEVA, Dinara (Pedagogy and Psychology, 2023)
The article deals with the pedagogical possibilities of part-time study in the conditions of lifelong learning in the digitalization of education and the tasks of creating favourable conditions for the organization of part-time study at a higher educational institution. It considers the logical connection of the concepts of "lifelong learning", "distance learning" and "part-time learning". The features of part-time study in vocational education are analyzed in comparison with full-time study. Study explores distance learning and part-time learning opportunities. In addition, he formulates the pedagogical conditions of extramural studies using digital technology in higher educational institutions. The study shows the opportunities for students to improve their professional knowledge or obtain an academic degree without having to leave work. It was concluded that correspondence education can be implemented on the basis of distance learning technology, open online courses, online communication.